Modernização da agricultura familiar em Sergipe : impasses e desafios da horticultura irrigada no Agreste de Itabaiana - Vasconcelos, Ramon Oliveira (2013)
The current study about the modernization of family agriculture in the wild of Itabaiana in Sergipe parsed the agricultural production irrigated from families who have embraced the irrigation as a means of in the production and with this, to increase the family income. In this sense, the research had as objective to parse the production and the reproduction of the irrigated horticulture with an emphasis in marketing of rural family units of the wild of Itabaiana in Sergipe. This was justified as a contribution to understand the formation, the social and economic role and the importance of the relationships amongst agriculture, workforce and the environment. To develop this work, it was set forth from direct and indirect observations of facts, through the field of work, with the application of interviews with various social actors, such as: farmers, middlemen, stallholders. In addition to these, it was necessary to apply interviews and raise data with federal, State and municipal bodies; and, finally, the bibliographical research. Therefore, the Agriculture of the region is a stain of the modernization process using irrigation, where there is the use of informational, scientific, technological innovations and policies which encourage the production. Family agriculture in the wild of Itabaiana in Sergipe is in a very visible and positive phase of transformation which is expressed by the production system. This demonstrates that a new standard of production, increasing income, is able to improve the conditions of life of the farmer and of the family.